From Observation to Intervention: A Critical Analysis of Treatment Timelines in Pediatric Empyema - Mumtaz Ahmed Qureshi, Imtiaz Ahmed Qureshi, Roshan Ali Siyal, Iqra Aslam (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Empyema thoracis is a significant cause of morbidity and mortality in children, especially in resource-poor countries where it tends to present late. The impact of the timing of treatment on outcomes is considerable, although there is little information from resource-poor countries. Objective: The objective of this study is to evaluate the treatment timelines from the onset of symptoms to definitive care in pediatric patients with empyema, and the factors associated with delayed care. Methods: A cross-sectional study was conducted at the Department of Pediatric Surgery, Liaquat University of Medical & Health Sciences, Jamshoro/Hyderabad, Pakistan, between August 2018 and July 2022. A total of 470 patients aged 5 months to 14 years, diagnosed with empyema thorax, were included in this study. The treatment period was classified into early (≤7 days), intermediate (8-14 days), and delayed (>14 days). Results: Mean age was 4.8±3.2 years, with a male preponderance (64.9%). Median time from onset of symptoms to intervention was 14 days (IQR: 9-21 days). Early, intermediate, and delayed interventions occurred in 21.9%, 38.1%, and 40% of patients, respectively. Delayed interventions were associated with higher complication rates (52.1% vs 11.7%, p<0.001), longer hospital stay (24.3±8.6 vs 10.2±3.4 days, p<0.001), and higher rate of thoracotomy (43.6% vs 5.8%, p<0.001). In multivariate analysis, independent predictors for delayed intervention were treatment in peripheral centers (aOR: 4.21), rural residents (aOR: 3.42), distance of travel >100km (aOR: 2.87), and lower socioeconomic status (aOR: 2.56). Conclusion: The timing of treatment has a significant influence on the outcome of empyema cases in children. Moreover, if treatment is delayed, several complications arise, such as invasive procedures. Early detection and referral programs play a critical role in improving treatment outcomes, especially in resource-limited settings. Keywords: Pediatric empyema, treatment timeline, delayed intervention, resource-limited setting, treatment outcomes.